Revitalizácia hnedouhoľného revíru Lužice - ako príklad zodpovedného a konkurencieschopného rozvoja banského regiónu po ukončení ťažby - Viera Krešáková (Ekonomika a Spoločnosť)
In 1988, the Lusatian lignite district was a major coal producer. However, after Germany's reunification in 1990 and subsequent deindustrialization, most lignite mines and power stations closed, causing significant job losses and left the landscape devastated. This paper presents an exploratory case study of projects aimed at the reclamation of opencast mines following the cessation of lignite mining. Using content analysis of the programme website, relevant studies, our own observations of several completed and ongoing projects, we present the IBA Fürst-Pückler-Land programme, which included 30 sub-projects aimed at revitalizing damaged areas after mining activity and were also intended to contribute to tackling unemployment and out-migration from the region. We illustrate the functioning of these projects through the example of the IBA terraces sub-project. The implemented projects have not only significantly improved the image and attractiveness of the mining-ravaged region, as evidenced by the increased number of tourists, but have also laid the groundwork for new initiatives aimed at halting severe depopulation and attracting skilled workers to the area. In the discussion, we formulate suggestions for inspiration of the Slovak Brown Coal District, which in 2023 also ceased the extraction of brown coal and its processing into electricity.